Effects of point of aim on the accuracy and eye movement behavior in bowling: A pilot study - Lim, J.; Chang, S. H.; Tomimbang, A. C. (International Journal of Kinesiology & Sports Science, 2018)
Background: A common research question in far-target aiming has been the importance and significance of the final visual fixation before movement initiation. In rolling tasks, such as 10-pin bowling, location of point of aim needs not be at the final target, the pins, but may be located at any point along the trajectory of the ball. Objective: Specific interest in the present experiment has focused on the relationship between visual point of aim and performance accuracy, and the relationship of visual control strategies utilized by expert performers. Methods: Skilled bowlers (N=7) performed 20 trials per condition concentrating on visual targets in different distances along the bowling lane (20, 40, 60 feet, and self-selected). Ball trajectory was tracked using a video based system and eye movement was measured using an eye tracking system. Results: Deviation of the ball from the visual target increased with visual target distance, while deviation of the ball from the pins was the lowest in the self-selected visual targets, followed by aiming at the pins. The final fixation duration before movement initiation was not associated with ball accuracy regardless of visual target locations. However, results demonstrated the association between final fixation duration task difficulty, that is, longer final fixation duration with increased visual target distance. Conclusion: The results indicate that visual fixations before movement initiation are uncharacteristically long while visual fixations just before the completion of the movement are relatively short.